Characterization of Low-Temperature Sensitivity and Chlorophyll Fluorescence in Yellow Leaf Mutants of Tomato - Shujing Ji; Yifan Zhang; Minghua Xu; Mingrui Zhao; Huixin Chen; Yongen Lu; Shengqun Pang; Wei Xu (Agronomy)
Leaf color mutants serve as valuable models for studying the regulation of plant photosynthesis, alternations in chloroplast structure and function, and the analysis of associated gene functions. A yellow leaf mutant, ylm, was separated from the wild tomato M82, with its yellowing intensity influenced by low temperature. To assess the low-temperature sensitivity of this mutant, the photosynthetic and chlorophyll fluorescence responses of ylm and M82 were examined under different temperature conditions. In this study, the ylm mutant and its wild type, M82, were exposed to three temperature levels, 16, 25, and 30 °C, for 48 h. The impact of these temperature treatments on leaf color change, chlorophyll content, photosynthetic performance, and chlorophyll fluorescence characteristics of mutant ylm was investigated. The results revealed the following: (1) After exposure to 16 °C, the ylm mutant exhibited significant yellowing, a marked reduction in chlorophyll content, and a notable increase in carotenoid content. At 25 °C, the differences were less pronounced, and at 30 °C, the differences between ylm and M82 were minimal. (2) The photosynthetic rate of the ylm mutant was lower than that of M82 at 16 °C, with the gap narrowing as temperature increased, eventually converging at higher temperatures. (3) The fluorescence transient curve (OJIP) of the ylm mutant differed significantly from that of M82 at 16 °C, with higher fluorescence intensity at the O point and lower intensity at the J, I, and P points. This difference was decreased at 25 °C and nearly disappeared at 30 °C. Additionally, the Fv/Fm, Fv/Fo, PIabs, PItotal, ABS/CSm, TRo/CSm, and ETo/CSm values of ylm were lower than those of M82 at 16 °C, while the ABS/RC and DIo/RC values were higher, with no significant differences observed at 30 °C. These findings suggest that the ylm mutant is highly sensitive to low temperature, with pronounced yellowing, reduced light energy absorption and capture efficiency, and impaired electron transport at lower temperature.